2004
DOI: 10.1021/jf0491613
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Biodegradable Films Obtained from Cysteine-Mediated Polymerized Gliadins

Abstract: This study focuses on the effect exerted by interchain disulfide bonds on the functional properties of films made from gliadins when cross-linked with cysteine. Gliadins were extracted from commercial wheat gluten with 70% aqueous ethanol, and cysteine was added to the film-forming solution to promote cross-linking between protein chains. The formation of interchain disulfide bonds was assessed by SDS-PAGE analysis. Gliadin films treated with cysteine maintain their integrity in water and become less extensibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…3 However, extensive research has shown that the gliadin and glutenin fractions of wheat gluten possess very different properties and render different results in both food and nonfood applications. 5,6,9,[13][14][15] Inspired by these findings, it was hypothesized that the aforementioned differences also may result in different adhesive performance, possibly rendering one of the fractions superior to that of the others or to wheat gluten. The aim of this study is to compare the tensile shear strength of wood substrates bonded with glutenin and gliadin, respectively, and to investigate the influence of application method and degree of penetration of the proteins into the wood material.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, extensive research has shown that the gliadin and glutenin fractions of wheat gluten possess very different properties and render different results in both food and nonfood applications. 5,6,9,[13][14][15] Inspired by these findings, it was hypothesized that the aforementioned differences also may result in different adhesive performance, possibly rendering one of the fractions superior to that of the others or to wheat gluten. The aim of this study is to compare the tensile shear strength of wood substrates bonded with glutenin and gliadin, respectively, and to investigate the influence of application method and degree of penetration of the proteins into the wood material.…”
Section: Introductionmentioning
confidence: 99%
“…They have excellent film forming character via solution casting using water and/or ethanol as co-solvent. In this sense, the unique physical and biochemical properties of gliadin make it suitable for numerous non-food applications such as biodegradable plastics, membranes and also as a material for biomedical applications [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Some of them have been associated with other analysis in order to develop a structural model [23] while others characterize and discuss the effect of heat, cold and denatured agents on conformers of a protein [3,4]. Indeed, all methods together provide the structural framework for the analysis of complex structures.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins are globular low molecular weight single-chains, readily soluble in aqueous ethanol. However, their solubility properties can be adjusted by using different solvents, which can promote kinetic intermediates which have been observed during folding from the unfolded state to the native state [1][2][3].…”
Section: Introductionmentioning
confidence: 99%